Harvard business review on knowledge management (Havard Business School Press, 1998)
This title presents leading minds and landmark ideas in an easily accessible format. From the preeminent thinkers whose work has defined an entire field to the rising stars who will redefine the way we think about business, "The Harvard Business Review Paperback" series delivers the fundamental information today's professionals need to stay competitive in a fast-moving world. The eight articles in "Harvard Business Review on Knowledge Management" highlight the leading-edge thinking and practical applications that are defining the field of knowledge management. Includes Peter Drucker's prophetic "The Coming of the New Organization" and Ikujiro Nonaka's "Knowledge-Creating Company". This is a "Harvard Business Review Paperback".